2012
DOI: 10.1007/s10585-011-9446-0
|View full text |Cite
|
Sign up to set email alerts
|

The anti-adhesive mucin podocalyxin may help initiate the transperitoneal metastasis of high grade serous ovarian carcinoma

Abstract: High grade serous ovarian tumors often metastasize transperitoneally, a process that begins when small tumor nodules de-adhere and are released into the fluid of the abdominal cavity where they float freely to reach new sites on the peritoneal wall. Podocalyxin, a small anti-adhesive sialomucin, has been shown to contribute to non-adhesive membrane domain formation in some epithelia and is overexpressed in a variety of cancers. We therefore assessed podocalyxin expression on a previously characterized tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 50 publications
7
59
0
Order By: Relevance
“…The antigenic determinant of the polyclonal PODXL antibody is amino acid residues 278–415, whereas our antibody reacts with amino acid residues 189–192. One proposal is that distinct membranous PODXL expression, but not cytoplasmic expression, associates with poor prognosis in different cancers [17,25]. Interestingly, staining by our monoclonal antibody was mainly cytoplasmic in cancer cells, with no distinct membranous immunopositivity.…”
Section: Discussionmentioning
confidence: 69%
“…The antigenic determinant of the polyclonal PODXL antibody is amino acid residues 278–415, whereas our antibody reacts with amino acid residues 189–192. One proposal is that distinct membranous PODXL expression, but not cytoplasmic expression, associates with poor prognosis in different cancers [17,25]. Interestingly, staining by our monoclonal antibody was mainly cytoplasmic in cancer cells, with no distinct membranous immunopositivity.…”
Section: Discussionmentioning
confidence: 69%
“…High expression of PODXL, in particular in the membrane of tumour cells, has previously been demonstrated to correlate to an impaired prognosis in many major cancer forms like breast cancer [9], colorectal cancer [1012], ovarian cancer [13], glioblastoma [14] and urothelial bladder cancer [15]. The results from this study further validate that membranous expression of PODXL is correlated to more aggressive tumours as it could not be demonstrated in non-invasive Ta-tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Strong, in particular membranous, expression has been found to correlate with more aggressive tumours and poor survival in many cancer forms such as breast cancer [9], colorectal cancer [1012], ovarian cancer [13], glioblastoma [14] as well as UBC [15]. In the latter study, we showed that PODXL is an independent risk factor for progressive disease and death in patients with all T-stages of UBC, as well as in the Ta/T1 subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…PODXL is known as a diagnostic marker and prognostic indicator in several cancers, including brain tumors, (6,16) prostate cancers, (17) testicular tumors, (2) renal cancers, (18) oral cancers, (19) thyroid cancers, (20) bladder cancers, (21) breast cancers, (22–24) ovarian cancers, (25) colorectal cancers, (26–29) pancreatic cancers, (30,31) and gastric cancers. (32) The glycans on PODXL bind to P-/E-/L-selectin expressed on platelets, endothelium, and leukocytes, respectively.…”
Section: Introductionmentioning
confidence: 99%